Humility versus Clericalism: Juan de Ávila and Pope Francis on Spiritual Formation and Reform - Bellitto, Christopher M. (Irish theological quarterly, 2025)
One of the hallmark targets of Pope Francis’s pontificate was clericalism and its attendant arrogance as roadblocks to the Church’s credibility, witness, and reform. In the Middle Ages, reformers were wary of the creeping worldliness and power politics that came with the creation of a papal monarchy. Looking at both history and the contemporary church, we might add caution against arrogant priests and prelates who see themselves as a cut above. What the Church then and now lacked in part was humility. This essay offers humility, a lost virtue, as a vaccine against religious and societal myopia and narcissism via a church history lesson from Juan de Ávila (1499–1569). Our consideration of Juan will be bracketed by considering first the situation today and then by examining how Pope Francis echoed this sixteenth-century reformer.